Synthesis of C2-tetrasubstituted indolin-3-ones via Cu-catalyzed oxidative dimerization of 2-aryl indoles and cross-addition with indoles. Issue 42 (2nd August 2019) - Singh, Anoop; Vanaparthi, Satheeshvarma; Choudhary, Sachin; Krishnan, Rangan; Kumar, Indresh
Abstract : A general protocol for the synthesis of 2, 2-disubstituted indolin-3-ones has been developed through self-dimerization of 2-aryl indoles and cross-addition with indoles under mild Cu-catalyzed oxidative conditions with good to high yields. Abstract : An efficient protocol for the synthesis of 2, 2-disubstituted indolin-3-ones under mild conditions has been developed. This reaction involves the copper-catalyzed in situ oxidative de-aromatization of 2-arylindoles to indol-3-one, followed by self-dimerization as well as cross-addition with indoles under mild conditions. The result generates a wide variety of C2-tetrasubstituted indolin-3-ones with good to high yields (62–82%).